Propositions About Intention to Choose Entrepreneurship Career Among Millenial Generation in Indonesia - Singgih Santoso1; Zaenal Mustafa EQ1; Sutarno2 (Communications of International Proceedings, 2020)
This literature study aims at examining the variables used to predict intention to choose an entrepreneurship career and the success of the business. Attitude to entrepreneurship, family support, and competency of being an entrepreneur conceptually have roles in explaining the intention to choose an entrepreneurship career and the success of the business. The millennial generation becomes the subjects of the generation who have a unique characteristic in doing business as entrepreneurs.
Keywords: Growth Intention; Business Success; Millennial Generation.